Fast microwave‐assisted hydrothermal synthesis of TiNb2O7 nanoparticles. Issue 4 (23rd October 2019) - Falk, Gilberto S.; Rodrigues Neto, João B.; Borlaf, Mario; Gómez, Sergio Y.; Novaes de Oliveira, Antonio P.; Hotza, Dachamir
Abstract: In this work, a fast method for synthesizing TiNb2 O7 nanoparticles was developed by combining colloidal sol‐gel and microwave‐assisted hydrothermal synthesis. The synthesis conditions and the subsequent thermal treatments were evaluated analyzing their effect on morphological, structural, and photocatalytic properties of the synthesized nanoparticles. The results indicated that the hybrid synthesis requires heating at temperature as low as 180°C for only 10 minutes. Therefore, this process is a feasible alternative method for obtaining nanoparticles with sizes ranging from 10 to 50 nm. Subsequent thermal treatments led to the direct crystallization of the TiNb2 O7 in the monoclinic phase, observing a direct correlation between the crystallinity and the photocatalytic activity: the higher the better. Abstract : The present article is an original and detailed study of the fast synthesis of nanoparticles of TiNb2O7 combining colloidal sol‐gel and microwave‐assisted hydrothermal synthesis, as well as, evaluated the photocatalytic potential of the synthesized nanoparticles. The article demonstrates that the synthesis conditions used were effective for obtaining nanoparticles with sizes varying from 10 to 50 nm. The article performed a copamparative between the times and temperatures of synthesis used to obtain TiNb2O7 demonstrating the potential of the methodology used.